SND1 regulates the androgen signaling axis by stabilizing EIF3B mRNA to facilitate the deterioration of prostate cancer - Ying Li; Chengru Yang; Guoli Cui; Shiliang Gui; Linlin Jia; Yu Chen; Honglin Niu; Hua Xin (Molecular Genetics and Genomics, 2026)

KaMYB71 positively regulates drought tolerance in Krascheninnikovia arborescens - Dazhuang Qi; Yuyi Hou; Huihui Liu; Xiaodong Yu; Linlin Zheng; Yingchun Wang (Plant Science, 2026)

The spatial divergence mechanism in the ecological resilience of Qinghai spruce to compound dry-hot extremes across the northeastern Qinghai-Tibet Plateau - Xuan Li; Xiaohua Gou; Dingcai Yin; Linlin Gao; Wenhuo Liu; Dingyun Zhang; Zibo Wang; Jianye Yu (Forest Ecology and Management, 2026)

Physics-informed machine learning of hyporheic exchange driven by channel blockage and riverbed morphodynamics - Hang Li; Linlin Li; Defu Liu; Genguang Zhang; Jiahao Zou; Yu Lei; Canyong Li (Journal of Hydrology, 2026)

Numerical simulation of regenerative accumulator for CO2 heat pump system in electric vehicles - Linlin Wang; Jiabao Ren; Rujie Yu; Baomin Dai; Tonghua Zou (International Journal of Refrigeration, 2026)

Corrigendum to “Regional genomic analysis of lineage distribution and transferable multidrug resistance among chicken-associated Salmonella Kentucky isolates in China” [Food Res. Int. 242 (2026) 120014] - Xueyuan Zhu; Wanting He; Ying Hu; Tantao Zhang; Yu Cheng; Peipei Cheng; Zhuosi Li; Xiaojie Qin; Qingli Dong; Linlin Xiao (Food Research International, 2026)

Regional genomic analysis of lineage distribution and transferable multidrug resistance among chicken-associated Salmonella Kentucky isolates in China - Xueyuan Zhu; Wanting He; Ying Hu; Tantao Zhang; Yu Cheng; Peipei Cheng; Zhuosi Li; Xiaojie Qin; Qingli Dong; Linlin Xiao (Food Research International, 2026)

Ginsenoside Rk1 reprograms ‘cold’ cancer cell membranes into a ‘hot’ antigen repertoire for highly immunogenic cancer vaccines - Fangming Dong; Linlin Qu; Lebin Wang; Jing Zhao; Zhiguang Duan; Xueqing Yu; Xiaoxuan Ma; Daidi Fan (Chemical Engineering Journal, 2026)

Representation of western boundary currents under different climatologies with varying horizontal resolutions - Hong Li; Guihua Wang; Fanghua Xu; Lijing Cheng; Junde Li; LinLin Zhang; Yuntao Wang; Wei Li; Haiqing Yu; Zenghong Liu; Zhijin Li (Progress in Oceanography, 2026)

Network toxicology and multi-omics reveal the mechanism of testicular toxicity induced by chronic AFB1 exposure in male quails - Zhenlei Ping; Yu Wang; Linlin Fu; Xiaoying Cui; Songtao Zheng; Xiaowen Jiang; Wenhui Yu (Journal of Hazardous Materials, 2026)

Genomics-driven risk assessment of antimicrobial resistance: Current status, challenges, and future perspectives - Peipei Cheng; Qian Wang; Wanting He; Xueyuan Zhu; Yu Cheng; Linlin Xiao; Qingli Dong (Food Research International, 2026)

Urea–NaHCO3 co-activated biochar enhances biohydrogen production via microbial community restructuring and metabolic pathway redirection - Tao Sheng; Jiaxing Meng; Chengwei Song; Changxing Yu; Caiyu Sun; Linlin Huang; Lixin Li; Chunxue Yang; Zhiwei Song (Environmental Research, 2026)

UniPept: A Universal Model for Predicting Peptide Properties Based on Atom-Residue Dual-Scale Integration - Haoshuang Wu; Yu Deng; Zhen Li; Mingming Qi; Yanshi Wei; Linlin Zhuo; Quan Zou; Wenqian Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Aurantio-Obtusin Attenuates Aβ-Induced Cognitive Impairment and Synaptic Dysfunction by Suppressing Neuroinflammation in Mice - Xueying Feng; Wei Yu; Song Guo; Yanyan Ji; Junhua Li; Ling Wang; Guolu Zhong; Shiyi Li; Linlin Niu; Danxin Zhu; Kan Zhou; Yehong Du (Journal of Neuroimmune Pharmacology, 2026)

Activating Na4 site via crystalline-phase-engineering enables charge redistribution and stress mitigation in Na4Fe3(PO4)2P2O7 cathodes - Linlin Zhou; Danjing Yang; Shuting Wen; Ling Chen; Chenwei Li; Haifeng Yu; Hao Jiang; Chunzhong Li (Science Bulletin, 2026)

Wave-driven core-shell structured cathode SMESs for remediation of phenanthrene and pyrene-contaminated offshore sediments - Haobo Yu; Boyue Liu; Hongying Yuan; Yankai Huang; Yinghao Huang; Tengfei Yuan; Linlin Li; Qi Deng; Jie Li (Journal of Hazardous Materials, 2026)

Role of M1 macrophage-derived exosomes in infantile hemangioma regression via AMPK/SIRT1/PGC1α pathway - LinLin Yue; XiuWen Zheng; XiaoQiang Wen; Yong Zeng; Wei Peng; QianDuo Li; LinShan Zeng; JinPing Liu; Yu Wang; WenQing Fu; HaiJin Liu; Feng Chen (Molecular & Cellular Toxicology, 2026)

Microbiological safety of dehydrated foods: risk analysis, technology evaluation, and synergistic strategies for next-generation processing - Yu Wang; Wenchao Liu; Linlin Li; Weiwei Cao; Junliang Chen; Chung Lim Law; Guangyue Ren; Xu Duan (Critical Reviews in Food Science and Nutrition, 2026)

Source-sink dynamics of WADA-prohibited compounds in coastal urban aquatic environments: From WWTP to bay - Min Zhou; Zifan Weng; Linlin Zhang; Shen Yu; Bing Hong; Yuxin Chen; Zhixing Yang; Qian Sun; Tao Ma; Dunming Xu (Journal of Environmental Management, 2026)

A barnacle-inspired hydrogel enables external-internal synergistic modulation of NF-κB/Nrf2 signaling for diabetic wound healing - Xuetong Ji; Junyao Li; Xintao Gao; Jiqing Dong; Linlin Ma; Yu Han; Xiangyan Chen; Yantao Li (Chemical Engineering Journal, 2026)

Distributed three-dimensional target enclosing control for AUVs under ocean currents - Linlin Shi; Haoming Wu; Biao Wei; Simin Lv; Yang Xu; Ronghao Zheng; Yu Chen (Ocean Engineering, 2026)

Lactiplantibacillus plantarum enables metal recovery from spent LiNi0.33Co0.33Mn0.33O2 cathode via EPS-mediated synergistic bioleaching - Min Li; Hong Wang; Danni Zhang; Zhong Li; Qiuli Xia; Xianjun Guan; Yaojie Yu; Linlin Tong; Junting Tong; Yongqiang Fan; Fuhui Wang; Dake Xu (Journal of Hazardous Materials, 2026)

Food-derived inositol derivatives mitigate high-fat diet-induced adiposity by attenuating inflammation and promoting adipocyte browning in mice - Xiaochen Guo; Mengjie Xu; Linlin Liu; Qinghui Lin; Rui Gao; Ruoxuan Xu; Wei Yu; Zhongmei Liang; Pengfei Wu; Zehan Dong; Zhen Xie; Nan Meng; et al. (Food Bioscience, 2026)

Responses of sedimentary magnetic susceptibility and metal contents to climate and anthropogenic activity changes: examination on lake records across the Asian monsoon region - Haiyang Yu; Shuangchi Liu; Jule Xiao; Xu Wang; Linlin Cui; Licheng Guo; Xueting Wang; Shihao Zhang (CATENA, 2026)

ABEEM/MM Magnesium Force Field for Proteins and Aqueous Solutions - Jing Zhang; Linan Lu; Runqiang Yu; Linlin Liu; Lei Wang; Cui Liu; Lidong Gong; Zhongzhi Yang (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Probiotics as a biocontrol strategy against Salmonella in poultry: A global meta-analysis - Mingjuan Qu; Lisheng Zhang; Jianlong Zhang; Xin Yu; Linlin Jiang; Hongwei Zhu; Xingxiao Zhang (Food Control, 2026)

Unlocking iron-chromium flow batteries: Conquering kinetics and crossover for affordable grid storage - Jiaxin Meng; Guozhen Zhang; Weizhai Bao; He Liu; Cong Guo; Jingfa Li; Feng Yu; Linlin Yang; Aishui Yu (Chemical Engineering Journal, 2026)

Spatiotemporal distribution, source apportionment, and ecological risks of polycyclic aromatic hydrocarbons in surface water of the Southern Ocean - Tao Yang; Linlin Shi; Saizhang Tan; Bangping Deng; Yu Ke; Shengming Cheng; Yubin Li; Shuangcheng Zhang; Jingwei Wu; Lichen Zhao; Jun Shi (Frontiers in Marine Science, 2026)
In Antarctica, low temperatures favor the trapping and deposition of polycyclic aromatic hydrocarbons (PAHs), whereas the biogeochemical cycling of PAHs on the Southern Ocean adjacent to Antarctica is highly sensitive to climate change. However, very little environmental and ecological information is available on interannual PAHs variations in the surface of the Southern Ocean. From 2022 to 2024, we employed the 38 th , 39 th , and 40 th Chinese National Antarctic Research Expeditions (CHINARE) to collect surface water samples and conduct analyses of the spatio-temporal distribution patterns, source apportionment, and probabilistic ecological risk assessment of the 16 USEPA priority PAHs. We found that ∑PAH concentration in the study area ranged from 427 to 5782 pg/L, with median values of 1795, 1736, and 2559 pg/L for the 38 th , 39 th , and 40 th expeditions, respectively, showing a latitudinal gradient pattern of higher concentrations at lower latitudes and lower concentrations at higher latitudes. A significant concentration rebound was observed in the 40th expedition. Integrated analysis using molecular diagnostic ratios, PCA, and PMF revealed that this rebound was driven by a distinct “dual-pressure pattern”: intensified logistical traffic emissions (combustion sources) and the persistent release of fresh, unweathered PAHs. Source apportionment indicated an evolutionary trend from mixed petrogenic and ship-related liquid fuel combustion (38th) to episodic fresh local inputs (39th), culminating in the complex superposition of sources in the 40th survey. Probabilistic risk assessment using Monte Carlo simulations confirmed that acute risks to plankton remain low (the 95th percentile of ∑RQ MPC was 0.077); However, a structural shift towards hydrophobic high-molecular-weight PAHs (increasing to ~18% in 2024) signals a rising hidden potential for biomagnification in keystone species like Euphausia superba . These findings provide a critical scientific baseline for identifying pollution sources and supporting Antarctic ecosystem management under changing environmental conditions.

DKK1 expression associates with tertiary lymphoid structure maturity in non-small cell lung cancer - Lin Ma; Linlin Yang; Junxu Wen; Fei Lu; Jinming Yu; Xiangjiao Meng (Apoptosis, 2026)

Eco-friendly asphalt: Emission reduction and performance enhancement with a novel fume suppressant - Shangheng Zeng; Ghim Ping Ong; Shi Xu; Hongyue Liu; Linlin Liu; Jianying Yu (Transportation Research Part D: Transport and Environment, 2026)

Source and accumulation of helium in the Dongsheng gas Field, Ordos Basin, China: Insights from noble gas isotopes - Yu Gao; Shuangjian Li; Xiaoqi Wu; Dongya Zhu; Pengpeng Li; Linlin Wang; Guangxiang Liu; Jiahao Lv; Jiarun Liu; Quanyou Liu (Journal of Asian Earth Sciences, 2026)

Multi-proxy provenance records from the Yanyuan Basin reveal the Cenozoic tectonic evolution along the southeastern Tibetan Plateau - Yuquan Jiang; Linlin Li; Xiangjiang Yu; Zhongtai He; Dewen Li; Yingying Li (Journal of Asian Earth Sciences, 2026)

Unlocking the anatomical code of flavor and lipids in grass carp (Ctenopharyngodon idellus) fish oil from different tissue parts by SPME-GC–MS, molecular docking, and lipidomics - Huijuan Zhou; Linchuan Xu; Junru Bai; Linlin Weng; Chengwei Yu; Mingming Hu; Bizhen Zhong; Jinlin Li; Zongcai Tu; Bin Peng (Food Chemistry, 2026)

Ecological niche shapes the composition and function of microbial communities in Astragalus membranaceus - Xiao Chen; Zhengyan Li; Yaogong Zhang; Chao Yao; Yuanshuai Yu; Feifei Ding; Jingyi Xu; Yuan Li; Linlin Dong; Guangfei Wei (Plant and Soil, 2026)

Mechanism of physicochemical changes in potato starch gel induced by citric acid-autoclaving for texture improvement and resistant starch formation - Linlin Cui; Xinzhu Wang; Shuhan Ge; Xia Li; Yu Wang; Bo Nan; Zhicheng Zhang; Yuhua Wang (Food Chemistry, 2026)

Meteorological observation research based on an improved EfficientNetV2 model - Haozheng Yin; Yu Cao; Linlin Liu; Dan Chen; Qiong Zhang (Environmental Modelling & Software, 2026)

The environmental niche of light purse seine vessels in the Arabian high seas - Shenglong Yang; Linlin Yu; Jiashu Shi; Weifeng Zhou; Tianfei Cheng; Keji Jiang; Yang Dai (Regional Studies in Marine Science, 2026)

The effect of yeaZ on formation and resuscitation of viable but nonculturable (VBNC) Salmonella enteritidis serovar enteritidis - Yuyang Jiao; Aiqi Yang; Xin Yu; Jiayu Yu; Jianlong Zhang; Linlin Jiang; Yao Li; Yang Liu; Hongwei Zhu; Xingxiao Zhang (Food Microbiology, 2026)

Widespread vegetation damage in Asian Interior due to the 2022 extreme drought - Yu Luo; Linlin Gao; Xiyue Fu; Linhan Si; Xinyue Li; Na Du; Yiyun Yuan; Xiang Zhang; Yang Deng (Environmental Research, 2026)

Inhalable tetrahedral DNA nanoplatforms for dual-barrier penetration and sustained deep-lung delivery of small-molecule drugs - Fenglin Jiang; Qi Han; Hao Deng; Jiaqi Li; Alimire Alifu; Zhuo Chen; Linlin Deng; Xiaoxiao Cai; Yu Chen; Yunfeng Lin (Chemical Engineering Journal, 2026)

Research hotspots and trends in Spartina alterniflora studies (1970–2023): A bibliometric analysis - Dandan Yan; Shanshan Wang; Peng Song; Yuqing Zhang; Yiming Huang; Yu Wang; Wenyan Zhu; Linlin Wu (Marine Pollution Bulletin, 2025)

LARS1 knockdown suppresses the biological activities of thyroid cancer cells by stimulating autophagy - Congwen Jin; Chuanhong Li; Linlin Chen; Hao Liu; Yousheng Yu; Benxin Chen (Tissue and Cell, 2025)

Learning to reason over multi-granularity knowledge graph for zero-shot urban land-use mapping - Yansheng Li; Yu Wang; Lei Yu; Bo Dang; Gang Xu; Zhenyu Zhong; Yuning Wu; Xin Guo; Kang Wu; Zheng Li; Linlin Wang; Jian Wang; et al. (Remote Sensing of Environment, 2025)

A LiDAR-based approach for real-time bulk coal extraction in cargo holds - Xinyi Yu; Dachuan Shi; Yuanlong Li; Kuiguang Jiao; Changrui Chen; Linlin Ou (Ocean Engineering, 2025)

Electroenhanced organic pollutant adsorption by three - dimensional isolated electrodes: Investigation of the “short - plate effect” - Xinyu Wang; Xiaochen Zhang; Linlin Chen; Fei Yu; Jie Ma (Journal of Cleaner Production, 2025)

Field study on the occurrence and risk assessment of haloacetamides in drinking water systems - Ying Yu; Ruya Chen; Linlin Pan; Baoyou Shi (Journal of Environmental Chemical Engineering, 2025)

Pilot-scale investigation of polyhydroxyalkanoates synthesis using mixed microbial cultures from fermented thermally hydrolyzed sludge - Yun He; Kuixiao Li; Yu Zhang; Gang Wang; Jing Chang; Shan Hao; Linlin Wei; Xu Xing (Bioresource Technology, 2025)

OWTDNet: A Novel CNN-Mamba Fusion Network for Offshore Wind Turbine Detection in High-Resolution Remote Sensing Images - Pengcheng Sha; Sujie Lu; Zongjie Xu; Jianhai Yu; Lei Li; Yibo Zou; Linlin Zhao (Journal of Marine Science and Engineering, 2025)
Real-time monitoring of offshore wind turbines (OWTs) through satellite remote sensing imagery is considered an essential process for large-scale infrastructure surveillance in ocean engineering. Current detection systems, however, are constrained by persistent technical limitations, including prohibitive deployment costs, insufficient discriminative power for learned features, and susceptibility to environmental interference. To address these challenges, a dual-branch architecture named OWTDNet is proposed, which integrates global contextual modeling via State Space Models (SSMs) with CNN-based local feature extraction for high-resolution OWTs detection. The primary branch utilizes a Mamba-structured encoder with linear computational complexity to establish long-range spatial dependencies, while an auxiliary Blurring-MobileNetv3 (B-Mv3) branch is designed to compensate for the local feature extraction deficiencies inherent in SSMs. Additionally, a novel Feature Alignment Module (FAM) is introduced to systematically coordinate cross-modal feature fusion between Mamba and CNN branches through channel-wise recalibration and position-aware alignment mechanisms. This module not only enables complementary feature integration but also enhances turbine-specific responses through attention-driven feature modulation. Comprehensive experimental validation demonstrated the superiority of the proposed framework, achieving a mean average precision (AP) of 47.1% on 40,000 × 40,000-pixel satellite imagery, while maintaining practical computational efficiency (127.7 s per image processing time).

Nonlinear trajectory tracking control of UVMS with compositing fuzzy disturbance observer and robust state-dependent Riccati equation - Qirong Tang; Yuanjie Di; Tong Li; Yuanzhe Cui; Zongwu Xie; Linlin Feng; Min Yu (Ocean Engineering, 2025)

Coupled effects of riverbed topography and entrainment probability on bedload transport in the Middle Yangtze River - Linlin Li; Yu Lei; Junqiang Xia; Meirong Zhou; Shanshan Deng; Yao Xiao; Hang Li; Maohua Le (Acta Geophysica, 2025)

A probabilistic formula for sediment incipient motion on combined sloping beds by considering the hiding-exposure effect - Linlin Li; Hang Li; Genguang Zhang; Yao Xiao; Defu Liu; Yu Lei; Maohua Le (Hydrological Sciences Journal, 2025)

Reduced Cytochrome c: Exploring Its Promoting Function in Synergistic Denitrification by Pseudomonas sp. JM-7 and Thiobacillus denitrificans - Bobo Xing; Ji Li; Linlin Li; Nigel J.D. Graham; Xian Li; Wenzheng Yu (Water Research, 2025)

Tetraether-based temperature record from Lake Xingyun in southwestern China since late MIS3 and implication for regional differences in temperature reconstruction - Haiyang Yu; Xu Wang; Ming Ji; Shihao Zhang; Gaochao Pan; Licheng Guo; Linlin Cui; Xueyun Ma; Wubiao Li; Dongsheng Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Land use carbon emission projections in shared socioeconomic and representative concentration pathways: Relationship with urbanization in Chinese megacities - Yu Yao; Linlin Lu; Zongtang Fu; Fang Chen; Ran Wang; Qingting Li (Land Use Policy, 2025)

Simultaneous accelerating H2O2 generation and activation via construction of CuS/NiS2 heterostructures in heterogeneous electro-Fenton for sulfamerazine degradation - Chenlin Wang; Chunhui Yu; Yuhan Ma; Fan Yang; Xinyang Sun; Kexin Wei; Junpu An; Li Li; Linlin Han; Kuobo Wang; Yongfeng Li (Journal of Environmental Chemical Engineering, 2025)

Sponge-like PNIPAM/Fe3O4/PPy composite hydrogel actuator with rapid response, self-sensing and multiple manipulating manners for complex application scenarios - Xingchen Cui; Bing Zhang; Pingzhi Shao; Linlin Li; Shunsheng Ye; Fuqiang Fan; Yu Fu; Fanbao Meng; Tieqiang Wang (Chemical Engineering Journal, 2025)

Advances in preclinical studies of ginsenoside Rh2 in antitumor therapy - Zheng Xu; Guanghuan Shen; Zhihua Xing; Jianghan Luo; Yu Zhu; Xuan Liu; ShiHao Li; Hao Wang; Linlin Cui (Medicinal Chemistry Research, 2025)

Electric vehicle attributed future air pollution alleviation: A case study in Guangdong province, China - Xinyu Yu; Man Sing Wong; Kai Qin; Rui Zhu; Linlin You; Jing Wei (Journal of Environmental Management, 2025)

Deep learning for wildfire risk prediction: Integrating remote sensing and environmental data - Zhengsen Xu; Jonathan Li; Sibo Cheng; Xue Rui; Yu Zhao; Hongjie He; Haiyan Guan; Aryan Sharma; Matthew Erxleben; Ryan Chang; Lincoln Linlin Xu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

In-situ phenolics enrichment of Camellia oleifera Abel oil via novel aqueous enzymatic extractions and its potential mechanism - Linlin Liu; Chengyu Jin; Yuanchao Lu; Ningxiang Yu; Xiaohua Nie; Qin Ye; Yuanxiang Jin; Xianghe Meng (Food Chemistry, 2025)

Melanoidins induced transformation of protein and polysaccharide during thermal hydrolysis-pyrolysis of sludge via non-covalent forces - Yimeng Jiao; Yifei Wu; Ziyang Dong; Jinxuan Ning; Jialin Wang; Lu Liu; Zhengda Lin; Yu Tian; Linlin Yin; Jun Zhang (Chemical Engineering Journal, 2025)

Determination of the deposition of urban submicron aerosols in the human respiratory tract considering hygroscopic growth - Aoyuan Yu; Jiayuan Lu; Xiaojing Shen; Xinyao Hu; Yangmei Zhang; Quan Liu; Hongfei Tong; Linlin Liang; Lei Liu; Qianli Ma; Lujie Han; Huizheng Che; et al. (Atmospheric Environment, 2025)

A preliminary study on the community structure of culturable planktonic and attached bacteria in the harbor of Qingdao, China - Shide Ma; Linlin Zhang; Yimeng Zhang; Yu Tai; Wen Han; Jinfeng Yang; Xin Shi; Bochao Lu; Jizhou Duan (Acta Oceanologica Sinica, 2025)

Social and ecological factors on the perception of cultural ecosystem services and disservices: Insights from Shanghai, China - Rongfei Su; Shiyu Ye; Linlin Yu; Jingbin Wu; Yan Kang; Ruishan Chen (Landscape and Urban Planning, 2025)

Synergistic effects on microstructural, rheological and functional properties of starch-enhanced processed mozzarella cheese - Linlin Tang; Jialin Liu; Ke Li; Yumeng Zhang; Shaomeng Luan; Tietao Chen; Hongjuan Li; Jinghua Yu (Food Structure, 2025)

Fertilization type affects the genetic potential for phosphorus mineralization but not for phosphorus solubilization at the continental scale - Yanhong Yuan; María Belén Barquero; Yu Li; Shuiqing Zhang; Hongzhu Fan; Huimin Zhang; Qiang Li; Shutang Liu; Linlin Shi; Andong Cai; Chengjie Ren; Minggang Xu; et al. (Applied Soil Ecology, 2025)

Insight into peroxidase-mediated Pinus massoniana resin browning, and browning inhibition strategy - Hanxiao Liu; Xiaopeng Chen; Dandan Yu; Siheng Zhang; Jiezhen Liang; Xin Li; Xiaojie Wei; Linlin Wang (Sustainable Chemistry and Pharmacy, 2025)

Construction of Fenton-like systems based on hierarchical nanoconfinement for efficient antibiotic removal - Linlin Su; Wei Hu; Xiaolun He; Chao Chen; Min Xu; Xiaoyu Yu; Yan Liu; Gang Yang; Lulu Long (Journal of Environmental Chemical Engineering, 2025)

Integration of lipidomics and flavoromics reveals the lipid-flavor transformation mechanism of fish oil from silver carp visceral with different enzymatic hydrolysis - Jinlin Li; Liping Yuan; Linlin Weng; Chengwei Yu; Mingming Hu; Bin Peng; Zongcai Tu (Food Chemistry, 2025)

Screening of hypoglycemic and probiotic properties of Pediococcus acidilactici FM-Pa-JXM94 and exploring the potential hypoglycemic mechanism - Ying Wang; Hui Zhang; Xingna Wang; Yu Zhang; Linlin Fan; Yanhong Ma; Xiaoli Liu (Food Bioscience, 2025)

Enhanced viability of Lactiplantibacillus plantarun by encapsulation with whey protein isolate fibrils and polysaccharides through layer-by-layer coating - Siyuan Li; Wei Su; Yu Zhang; Wanling Gan; Xiaoli Liu; Linlin Fan (Food Hydrocolloids, 2025)

Tendon injury repair strategy driven by supramolecular hydrogen bonding and dynamic covalent bond self-assembly microspheres - Taishan Liu; Xiaoxuan Ma; Chenhui Zhu; Yu Mi; Jing Zhao; Linlin Qu; Huan Lei; Daidi Fan (Chemical Engineering Journal, 2025)

The Receptor for Advanced Glycation End-products in the Mouse Anterior Cingulate Cortex is Involved in Neuron‒Astrocyte Coupling in Chronic Inflammatory Pain and Anxiety Comorbidity - Wei Jiang; Minmin Gong; Linlin Shen; Chenghui Yu; Huaizhen Ruan; Penghui Chen; Shihao Gao; Zhi Xiao (Molecular Neurobiology, 2025)

Nine-year biochar history increases topsoil nitrogen stocks and reduces the refractory organic nitrogen fractions in deep soils - Di Wang; Shuai Liu; Liwei Hao; Qi Yue; Linlin Jiang; Yu Lan; Wenfu Chen (Journal of Soils and Sediments, 2025)

Spegazzinia menglaensis, A Novel Species of Didymosphaeriaceae from Air in China - Xingwen Dai; Linlin Fang; Tong Chen; Manyao Feng; Zefen Yu (Current Microbiology, 2025)

Computational fluid dynamics and machine learning assisted Al-LDH adsorbent reactor design for lithium recovery from salt lakes - Jiangtao Yu; Minmeng Tang; Peng Cui; Jianquan Deng; Haiying Mi; Li Zhang; Linlin Chen; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2025)

Transcranial Magnetic Stimulation Alleviates Spatial Learning and Memory Impairment by Inhibiting the Expression of SARM1 in Rats with Cerebral Ischemia–Reperfusion Injury - Linlin Jiang; Yule Wang; Yingxi He; Ying Wang; Hao Liu; Yu Chen; Jingxi Ma; Ying Yin; Lingchuan Niu (NeuroMolecular Medicine, 2025)

Modeling of sediment exchange process and channel evolution in the downstream reach below the Three Gorges Dam - Linlin Li; Junqiang Xia; Meirong Zhou; Shanshan Deng; Defu Liu; Hang Li; Yu Lei (CATENA, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Influence of ocean-atmosphere interactions on typhoon track and intensity: a case study for typhoon “Hato” (1713) - Yonghang Chen; Yu Wei; Yunxia Zheng; Xianwen Wu; Qiong Liu; Ruixue Li; Linlin Sun; Bingke Zhao; Sijie Yin; Haicheng Liu; Xiaoyu Li (Natural Hazards, 2025)

Environmental heterogeneity drives the spatial distribution of macrobenthos in the Yellow River Delta wetland - Qinglu Fu; Jiao Wang; Debin Sun; Jianyu Chi; Wenzheng Fan; Yu Li; Yilin Wang; Baoquan Li; Linlin Chen (Aquatic Sciences, 2025)

Exploring Boundary Layer Physics and Atmospheric Chemistry in Megacities: Insights from the Beijing 325 m Meteorological Tower - Yele Sun; Zifa Wang; Linlin Wang; Xueling Cheng; Weiqi Xu; Yu Shi; Wei Zhou; Yan Li; Fei Hu; Zhiqiu Gao; Zhongxiang Hong (Advances in Atmospheric Sciences, 2025)

Exosomal miR-27a-5p attenuates inflammation through Toll-like receptor 7 in foodborne Salmonella infections - Mingjuan Qu; Shengfa Su; Linlin Jiang; Xin Yu; Jianlong Zhang; Hongwei Zhu; Kexue Han; Xingxiao Zhang (Veterinary Microbiology, 2025)

Host selection shapes structure and network of microbial community of Epimedium plants along the soil–rhizosphere–plant continuum - Zhaoyu Zhang; Ziying Huang; Xiao Chen; Guozhuang Zhang; Mengzhi Li; Anning Li; Xiaolin Lin; Yuxin Zhou; Yu Zhang; Shilin Chen; Linlin Dong; Guangfei Wei (Rhizosphere, 2025)

Sustainable futures for transformational forestry resource-based city: Linking landscape pattern and administrative policy - Linlin Xu; Hu Yu; Linsheng Zhong (Journal of Cleaner Production, 2025)

Physicochemical properties and structure of rice dough and protein based on TGase combined with sodium metabisulfite modification - Xuyang Ren; Wanshan Yang; Huining Zhang; Yang Yu; Xiaofeng Hu; Hongchen Fan; Linlin Liu; Mingshou Lv; Ying Sun; Yanguo Shi; Yanling Hao; Fenglian Chen (Food Chemistry, 2025)

Novel NIR-Ⅱ-Activated titanate-supported iridium nanoplatform delivers multimodal antitumor therapy synergistic with PD-1 inhibition in TNBC - Peixin Du; Xian Jiang; Zihan Xu; Linlin Song; Meixu Chen; Yujie Zhao; Jing Yu; Tianyue Xu; Ting Sun; Huang Zhu; Hubing Shi; Jing Jing (Chemical Engineering Journal, 2025)

Effects of cadmium (Cd) on photosynthetic characteristics and chlorophyll fluorescence parameters in the ornamental Plant Salvia splendens Ker-Gawl - Lian Jia; Guangchao Yu; Zhen Zhao; LinLin Lü (Physiology and Molecular Biology of Plants, 2025)

Bivariate Spatial Autocorrelation Analysis of Keshan Disease and Hair Selenium of Residents in Heilongjiang Province, China - Jiacheng Li; Guijin Li; Cheng Wang; Huixin Sun; Linlin Du; Shuxiu Hao; Qingyu Zeng; Cunqi Lv; Yu Zhang; Xinshu Wang; Zhifeng Xing; Tong Wang (Biological Trace Element Research, 2025)

Spatial Clusters of Low Serum Selenium: the Priorities of Selenium Supplementation to Residents of Keshan Disease Endemic Areas - Qingyu Zeng; Guijin Li; Ruixiang Wang; Cunqi Lv; Shuxiu Hao; Jiacheng Li; Huixin Sun; Linlin Du; Cheng Wang; Yu Zhang; Xinshu Wang; Yuehui Jia; et al. (Biological Trace Element Research, 2025)

A dual deep learning approach for winter temperature prediction in solar greenhouses in Northern China - Jingxin Yu; Jinpeng Zhao; Congcong Sun; Ruochen Zhang; Wengang Zheng; Linlin Xu; Xiaoming Wei (Computers and Electronics in Agriculture, 2025)

Failure and post-failure kinematic disaster processes of columnar rock masses based on 3D discontinuous deformation analysis - Ke Ma; Shengze Zhao; Guoyang Liu; Jianbin Miao; Jiashuo Kang; Linlin Wang; Qun Yu (International Journal of Rock Mechanics and Mining Sciences, 2025)

Protective effect of Apelin-13 on oxygen and glucose deprivation induced-damage in retinal ganglion cells cultured in vitro - Li Dai; Linlin Luo; Ya Zhang; Min Fu; Ling Yu (Journal of Molecular Histology, 2025)

Indian summer monsoon variations since late MIS3: A perspective from multiproxy evidence from Lake Xingyun in southwestern China - Haiyang Yu; Linlin Cui; Xu Wang; Xueyun Ma; Bing Xu; Wubiao Li; Xueting Wang (Quaternary International, 2025)

BI1 Activates Autophagy and Mediates TDP43 to Regulate ALS Pathogenesis - Yu Wang; Yuxiang Wang; Hanlan Yin; Zixuan Xiao; Zhichao Ren; Xueting Ma; Jingtian Zhang; Xueqi Fu; Fuqiang Zhang; Linlin Zeng (Molecular Neurobiology, 2025)

Threshold of sediment incipient motion on a three-dimensional riverbed by considering the hiding-exposure effect with experimental investigations - Linlin Li; Yao Xiao; Genguang Zhang; Yu Lei; Hang Li; Defu Liu (Acta Geophysica, 2024)

Total water level prediction at continental scale: Coastal ocean - Linlin Cui; Fei Ye; Y. Joseph Zhang; Haocheng Yu; Zhengui Wang; Saeed Moghimi; Gregory Seroka; Jack Riley; Shachak Pe'eri; Soroosh Mani; Edward Myers; Kyungmin Park; et al. (Ocean Modelling, 2024)

Simulation of diffusion of combustible refrigerants R1234yf and R290 leakage in automotive air conditioning - Linlin Wang; Yu He; Jiabao Ren; Dan Wang; Baomin Dai; Zhe Zhang (International Journal of Refrigeration, 2024)

The role of probiotics in the treatment of non-alcoholic fatty liver disease (NAFLD): New insights based on meta-analysis and subgroup analysis - Rui Xiao; Yang Cao; Linlin Wang; Peijun Tian; Qixiao Zhai; Jianxin Zhao; Gang Wang; Yu Zhu (Food Bioscience, 2024)

Non-coding RNA notations, regulations and interactive resources - Mengwei Cheng; Yinhuan Zhu; Han Yu; Linlin Shao; Yiming Zhang; Lanxing Li; Haohong Tu; Luyao Xie; Haoyu Chao; Peijing Zhang; Saige Xin; Cong Feng; et al. (Functional & Integrative Genomics, 2024)

Effects of nitrogen fertilization on nitrogen metabolism and grain protein in premium-tasty japonica rice - Yunsheng Song; Minghui Dong; Yajie Hu; Linlin Shi; Junrong Gu; Yuxuan Wang; Shikun Wang; Penghui Cao; Yajie Yu; Yongliang Zhu; Yulin Xie; Zhongying Qiao; et al. (Cereal Research Communications, 2024)

Genes and Pathways Underpinning Klinefelter Syndrome at Bulk and Single-Cell Levels - Linlin Tian; Yan Yu; Ziqing Mao; Dandan Xu; Hongbo Zhang; Mengkai Qiao; Tong Chen; Wen Liu (Biochemical Genetics, 2024)

Insights of using microbial material in fluoride removal from wastewater: A review - Linlin Cui; Junjun Wang; Hao Zhou; Shiyu Shao; Jue Kang; Xinyi Yu; Hongbo Zhao; Li Shen (Journal of Environmental Management, 2024)

High-value multilayer graphene oxide prepared by catalytic pyrolysis of petroleum tar and applications: Trash to treasure - Lu Liu; Jialin Wang; Yifei Wu; Linlin Yin; Wei Zuo; Yu Tian; Jun Zhang (Chemical Engineering Journal, 2024)

The Environmental Niche of the Light Purse Seine Fleet in the Northwest Pacific Ocean Based on Automatic Identification System Data - Shenglong Yang; Lijun Wan; Linlin Yu; Jiashu Shi; Weifeng Zhou; Shengmao Zhang; Fei Wang; Zuli Wu; Yang Dai; Keji Jiang; Wei Fan (Journal of Marine Science and Engineering, 2024)
Ecosystem-based fisheries management requires high-precision fisheries information to provide relevant data for natural resource management, assessment, and marine spatial planning. This study utilizes Automatic Identification System (AIS) data from light purse seine vessels from the Chinese mainland that were collected from May to November between 2020 and 2022, along with the corresponding environmental data. By applying boosted regression trees (BRTs) and generalized additive models (GAMs), this study establishes nonlinear relationships between fishing intensity and predictor variables and explores the ecological and environmental drivers behind the spatial distribution of light purse seine vessels from the Chinese mainland in the Northwest Pacific. This research identifies the key influencing factors and reveals significant seasonal preferences for different marine environments in various months, with chlorophyll-a being the primary influencing factor. The predicted fishing effort closely resembles observed data, providing valuable information to support fisheries resource management and planning.

Environmental exposure patterns to 94 current-use pesticides in women of reproductive age who are preparing for pregnancy - Tian Tian; Fang Liu; Yu Fu; Junjie Ao; Shujian Lin; Qianhui Cheng; Kalbinur Kayim; Fei Kong; Linlin Wang; Xiaoyu Long; Yuanyuan Wang; Jie Qiao (Science of The Total Environment, 2024)

3D-printed devices for continuous-flow lithium recovery of brines - Jiangtao Yu; Jie Zhu; Zhuo Han; Peng Cui; Haiying Mi; Anan Zhang; Linlin Chen; Xiaowei Li; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2024)

Finer topographic data improves distribution modeling of Picea crassifolia in the northern Qilian Mountains - Xiang Zhang; Linlin Gao; Yu Luo; Yiyun Yuan; Baolong Ma; Yang Deng (Journal of Mountain Science, 2024)

The recent high occurrence of spring atmospheric droughts over central Hengduan Mountains is unprecedented in 669-year tree-ring records - Linlin Cui; Jinjian Li; Wenling An; Ningsheng Qin; Huiming Song; Yu Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Study on China’s Farmland–Grain resource curse: Empirical testing based on 31 Provinces and 2843 Counties - Renyi Yang; Changbiao Zhong; Zisheng Yang; Shiqin Yang; Guanqiu Ji; Jingke Yu; Linlin Cao; Jinrong Yang; Lei Luo; Yicong Shen; Yongdong Zhang (Land Use Policy, 2024)

Exploring biomass addition in methanol production: A life cycle analysis of efficiency and environmental impacts - Linlin Liu; Shenghui Li; Yu Zhuang; Jian Du (Journal of Cleaner Production, 2024)

Unraveling the dynamics of bed and breakfast clusters development: A multiscale analysis - Hu Yu; Linlin Xu (Applied Geography, 2024)

Elevated [CO2] reduces CH4 emissions from rice paddies under in situ straw incorporation - Ting Bao; Ling Wang; Yuanfa Huang; Huixin Li; Lanying Qiu; Jiujie Liu; Linlin Shi; Yunlong Liu; Haoyu Qian; Yanfeng Ding; Yu Jiang (Agriculture, Ecosystems & Environment, 2024)

Low energy-consumption oriented membrane fouling control strategy in anaerobic fluidized membrane bioreactor - Lu Liu; Ze Guo; Yihe Wang; Linlin Yin; Wei Zuo; Yu Tian; Jun Zhang (Chemosphere, 2024)

Insight into the mechanisms involved in the improved antagonistic efficacy of Pichia caribbica against postharvest black spot of tomato fruits by combined application with oligochitosan - Xiaoyun Zhang; Yu Xin; Qingrong Yue; Esa Abiso Godana; Linlin Gao; Mengge Dou; Hongyao Zhou; Jun Li; Lina Zhao; Hongyin Zhang (Postharvest Biology and Technology, 2024)

Volcanic lithofacies control the space in unconventional, rhyolitic hydrocarbon reservoirs: The Hailar Basin, NE China - Yuting Chen; Han Zheng; Guido Ventura; Linlin Zeng; Wei Pi; Yu Wei (Marine and Petroleum Geology, 2024)

Mitigation measures of storm surge inundation at an onshore aquaculture farm - Linlin Wang; Shikun Hu; Jing-Cheng Han; Peng Hu; Xuan Yu (Journal of Hydrology, 2024)

Coupling sedimentary records of anthropogenic metal(loid)s in urban waterscape parks with the “Coal to Gas” transition - Shen Yu; Tao Ma; Linlin Zhang; Qi Li; Min Zhou (Journal of Hazardous Materials, 2024)

Microglial exosomes in paraquat-induced Parkinson's disease: Neuroprotection and biomarker clues - Jingwen Wu; Wenya Shao; Xu Liu; Fuli Zheng; Yaping Wang; Ping Cai; Zhenkun Guo; Hong Hu; Guangxia Yu; Jianhui Guo; Linlin Yao; Siying Wu; et al. (Environmental Pollution, 2024)

Source-sink relationships of anthropogenic metal(loid)s from urban catchment to waterway in relation to spatial pattern of urban green infrastructures - Juan Li; Linlin Zhang; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Journal of Hazardous Materials, 2024)

A novel metal–organic framework based electrochemical immunosensor for the rapid detection of Salmonella typhimurium detection in milk - Ke Zhan; Linlin Chen; Shanshan Li; Qiuying Yu; Zheng Zhao; Junwei Li; Yunrui Xing; Hongtao Ren; Na Wang; Gaiping Zhang (Food Chemistry, 2024)

Response of photosynthetic characteristics and antioxidant system in the leaves of safflower to NaCl and NaHCO3 - Linlin Song; Yongliang Yu; Hongzhi Chen; Yuwei Feng; Shuo Chen; Huihui Zhang; Haijia Zhou; Li Meng; Yue Wang (Plant Cell Reports, 2024)

Effects of Nitrogen Fertilizer Reduction Combined with Foliar Fertilizer Application on the Physiological Characteristics and Yield of High-Quality Japonica Rice - Yunsheng Song; Minghui Dong; Fei Chen; Yajie Hu; Yongliang Zhu; Junrong Gu; Peifeng Chen; Yulin Xie; Caiyong Yuan; Zhongying Qiao; Yajie Yu; Penghui Cao; et al. (International Journal of Plant Production, 2024)

EB-Net: an efficient balanced network for accuracy and speed of remote sensing detection - Dehua Zhang; Dechen Wang; Changcheng Yu; Xinyuan Hao; Linlin Liang (International Journal of Remote Sensing, 2024)

Change characteristics, bacteria host, and spread risks of bioaerosol ARGs/MGEs from different stages in sewage and sludge treatment process - Yanjie Wang; Kai Yang; Lin Li; Liying Yang; Song Zhang; Fangfang Yu; Linlin Hua (Journal of Hazardous Materials, 2024)

Construction of Ni3S4@ZIS@C3N5 photocatalyst with type II and Z-type heterojunctions by self-assembly for efficient photocatalytic hydrogen evolution - Huixiang Yan; Wei Li; Huixing Yang; Yongzhuo Yu; Chaoyu Lv; Linlin Hou; Wenxu Zhang; Di Lin; Shichao Jiao (Environmental Research, 2024)

Promoting denitrification via high electron conversion ratio in the iron valence Cycle: Prospects for Pseudomonas sp. JM-7 application in environmental engineering - Bobo Xing; Ji Li; Linlin Li; Nigel J.D. Graham; Binghao Zhao; Xian Li; Wenzheng Yu (Chemical Engineering Journal, 2024)

Influence of meteorological factors on open biomass burning at a background site in Northeast China - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Journal of Environmental Sciences, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Mild low-temperature photothermal therapy demonstrated a distinctive 'hot spring' effect in the multichannel regulation of atherosclerosis instead of inducing foam cell apoptosis - Jie Sheng; Ziyue Zu; Jianchen Qi; Yugang Zhang; Haoguang Wu; Zhicheng Wang; Yu Miao; Tao Zheng; Sheng Wang; Linlin Zhang; Guangming Lu; Longjiang Zhang (Chemical Engineering Journal, 2024)

Medium optimization and dust suppression performance analysis of microbial-based dust suppressant compound by response surface curve method - Xiangming Hu; Zhiyuan Yang; Yanyun Zhao; Yue Dong; Chengcheng Wang; Linlin Zhang; Yiyun Yu; Kai Wu; Liyan Ren (Environmental Science and Pollution Research, 2024)

Deterioration of single-use biodegradable plastics in high-humidity air and freshwaters over one year: Significant disparities in surface physicochemical characteristics and degradation rates - Lingling Hu; Linlin He; Li Cai; Yumeng Wang; Gang Wu; Daoyong Zhang; Xiangliang Pan; Yu-Zhong Wang (Journal of Hazardous Materials, 2024)

Observational insights into the environmental effect for secondary inorganic aerosol formation in the Northeast China: Influence of biomass burning - Yulong Wang; Linlin Liang; Wanyun Xu; Chang Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Xiaobin Xu; Dajiang Yu; Peng Wang; Qingli Song; Jiumeng Liu; et al. (Atmospheric Research, 2024)

Spatio-temporal variability of fishing habitat suitability to tuna purse seine fleet in the Western and Central Pacific Ocean - Shenglong Yang; Lijun Wang; Yingjie Fei; Shengmao Zhang; Linlin Yu; Heng Zhang; Fei Wang; Yumei Wu; Zuli Wu; Wei Wang; Jiayu Shi; Keji Jiang; et al. (Regional Studies in Marine Science, 2024)

Forward numerical investigation of potential tsunami deposits in the South China sea: A case study of Nan'ao Island - Fating Li; Linlin Li; Fengling Yu; Kangyou Huang; Adam D. Switzer (Marine and Petroleum Geology, 2024)

Electrocatalytic degradation of nitrogenous heterocycles on confined particle electrodes derived from ZIF-67 - Yu Liu; Linlin Qin; Yiming Qin; Tong Yang; Haoran Lu; Yulong Liu; Qiqi Zhang; Wenyan Liang (Journal of Hazardous Materials, 2024)

Controllable synthesis of polyaspartic acid: Studying into the chain length effect for calcium scale inhibition - Meng-Long Zhang; Zheng Ruan; Yu Han; Zhi-Wei Cao; Linlin Zhao; Yuan-Qing Xu; Zhong-Yan Cao; Wen-Yan Shi; Ying Xu (Desalination, 2024)

Sulfur-Doped porous carbon Adsorbent: A promising solution for effective and selective CO2 capture - Jiali Bai; Jiawei Shao; Qiyun Yu; Muslum Demir; Bilge Nazli Altay; Turgunov Muhammad Ali; Yongfu Jiang; Linlin Wang; Xin Hu (Chemical Engineering Journal, 2024)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Hippocampal subfield volumes in mild cognitive impairment and alzheimer’s disease: a systematic review and meta-analysis - Jinhuan Zhang; Linlin Xie; Changjiang Cheng; Yongfeng Liu; Xiaodong Zhang; Haoyu Wang; Jingting Hu; Haibo Yu; Jinping Xu (Brain Imaging and Behavior, 2023)

Investigating the influence of bentonite colloids on strontium sorption in granite under various hydrogeochemical conditions - Fangfei Cai; Funing Ma; Xiaoying Zhang; Paul Reimus; Linlin Qi; Yu Wang; Di Lu; Hung Vo Thanh; Zhenxue Dai (Science of The Total Environment, 2023)

A review of adsorption materials and their application of 3D printing technology in the separation process - Jiangtao Yu; Jie Zhu; Linlin Chen; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Chemical Engineering Journal, 2023)

Solar forcing and ENSO regulated rates of change of ecosystems in Northeast China since the last deglaciation - Guizai Gao; Honghao Niu; Lina Song; Jiangyong Wang; Meng Meng; Zhuo Yang; Linlin Liu; Yuanxiang Wei; Niankang Chen; Jihuai Yu; Dongmei Jie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Multi-valent mRNA vaccines against monkeypox enveloped or mature viron surface antigens demonstrate robust immune response and neutralizing activity - Niubing Zhang; Xiang Cheng; Yilong Zhu; Ouyang Mo; Huiqing Yu; Liqi Zhu; Juan Zhang; Linlin Kuang; Ying Gao; Ruiyuan Cao; Xiaozhen Liang; Haikun Wang; et al. (Science China Life Sciences, 2023)

Contrasting effects of rice husk and its biochar on N2O emissions and nitrogen leaching from Lei bamboo soils under subtropical conditions - Rong Zhou; Zhe Chen; Ali EI-Naggar; Linlin Tian; Chengpeng Huang; Zhen Zhang; Kumuduni Niroshika Palansooriya; Yongfu Li; Bing Yu; Scott X. Chang; Yanjiang Cai (Biology and Fertility of Soils, 2023)

Urinary phthalate metabolites and heart rate variability: A panel study - Ziqian Zhang; Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Jie Yu; Huihua Yang; Xuefeng Lai; Xiaomin Zhang; Liangle Yang (Environmental Pollution, 2023)

3D-printed titanium-based ionic sieve monolithic adsorbent for selective lithium recovery from salt lakes - Jiangtao Yu; Jie Zhu; Guiling Luo; Linlin Chen; Xiaowei Li; Peng Cui; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2023)

Effect of Environmental Factors on Performance of Bioreactor with Immobilized Petroleum-Degrading Bacteria Beads - Yixuan Liu; Yue Dun; Jianliang Xue; Yu Gao; Dongle Cheng; Yanlu Qiao; Linlin Zhang (Water, Air, & Soil Pollution, 2023)

Evolution of the landscape pattern in the Xin'an River Basin and its response to tourism activities - Linlin Xu; Hu Yu; Linsheng Zhong (Science of The Total Environment, 2023)

Glyphosate induces autophagy in hepatic L8824 cell line through NO-mediated activation of RAS/RAF/MEK/ERK signaling pathway and energy metabolism disorders - Linlin Zhang; Lu Chen; Meng Qi; Fuchang Yu; Xiaotong Ni; Haozheng Hong; Haotian Xu; Shiwen Xu (Fish & Shellfish Immunology, 2023)

Tannin alleviates glyphosate exposure-induced apoptosis, necrosis and immune dysfunction in hepatic L8824 cell line by inhibiting ROS/PTEN/PI3K/AKT pathway - Linlin Zhang; Lu Chen; Dayong Tao; Fuchang Yu; Meng Qi; Shiwen Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Long-term non-phosphorus application increased paddy methane emission by promoting organic acid and methanogen abundance in Tai Lake region, China - Chen Xu; Susu Shen; Beibei Zhou; Yuanyuan Feng; Zhu He; Linlin Shi; Yu Wang; Haihou Wang; Tripti Mishra; Lihong Xue (Science of The Total Environment, 2023)

Global, regional, and national deaths, disability-adjusted life years, years lived with disability, and years of life lost for the global disease burden attributable to second-hand smoke, 1990–2019: A systematic analysis for the Global Burden of Disease Study - Chunxia Zhai; Dingtao Hu; Guanghui Yu; Wanqin Hu; Qiqun Zong; Ziye Yan; Yuhua Wang; Linlin Wang; Tingyu Zhang; Hongyu Sun; Ling Cai; Liangyu Cui; et al. (Science of The Total Environment, 2023)

A High Concentration of Polycyclic Aromatic Hydrocarbons in Umbilical Cord Tissue is Associated with an Increased Risk for Fetal Neural Tube Defects - Shengju Yin; Ying Sun; Jinhui Yu; Zaiming Su; Mingkun Tong; Yali Zhang; Jufen Liu; Linlin Wang; Zhiwen Li; Aiguo Ren; Lei Jin (Exposure and Health, 2023)

Phthalate Mixture Exposure is Associated with Elevated Blood Pressure in Chinese Children: A Panel Study - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Meng Li; Shuang Chen; Jie Yu; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Exposure and Health, 2023)

Impact of diurnal temperature range on other infectious diarrhea in Tongcheng, China, 2010–2019: a distributed lag non-linear analysis - Linlin Wang; Jian Cheng; Guanghui Yu; Qiqun Zong; Chunxia Zhai; Wanqin Hu; Yuhua Wang; Ziye Yan; Tingyu Zhang; Junwu Wang; Chengye Zhang; Hong Su; et al. (Environmental Science and Pollution Research, 2023)

Spatial effects of urban green infrastructure on instream water quality assessed by chemical and sensory indicators - Juan Li; Shen Yu; Bing Hong; Ruihan Lin; Qi Li; Linlin Zhang; Tao Lin; Haifeng Jia; Dawen Yang; Chengwei Gu; Qimeng Jia (Science of The Total Environment, 2023)

Air pollution exposure and ovarian reserve impairment in Shandong province, China: The effects of particulate matter size and exposure window - Lihong Pang; Wenhao Yu; Jiale Lv; Yunde Dou; Han Zhao; Shanshan Li; Yuming Guo; Gongbo Chen; Linlin Cui; Jingmei Hu; Yueran Zhao; Qi Zhao; et al. (Environmental Research, 2023)

Multi-scale ocean dynamical processes in the Indo-Pacific Convergence Zone and their climatic and ecological effects - Yan Du; Fan Wang; Tianyu Wang; Weiwei Liu; Linlin Liang; Ying Zhang; Yunfan Chen; Jiaxing Liu; Wei Wu; Kefu Yu; Jing Zhang (Earth-Science Reviews, 2023)

Preparation of high hydrophilic H2TiO3 ion sieve for lithium recovery from liquid lithium resources - Jing Sun; Xiaowei Li; Yuhong Huang; Guiling Luo; Duanjian Tao; Jiangtao Yu; Linlin Chen; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Otus scops adenovirus: the complete genome sequence of a novel aviadenovirus discovered in a wild owl - Weibo Zheng; Tingshu Jiang; Zhe Zhang; Dong Pan; Wenli Tang; Youzhi Li; Linlin Jiang; Hongwei Zhu; Xin Yu; Guozhong Chen; Jiao Wang; Jianlong Zhang; et al. (Archives of Virology, 2023)

The Environmental Niche of the Tuna Purse Seine Fleet in the Western and Central Pacific Ocean Based on Different Fisheries Data - Shenglong Yang; Linlin Yu; Fei Wang; Tianfei Chen; Yingjie Fei; Shengmao Zhang; Wei Fan (Fishes, 2023)
Understanding the spatial pattern of human fishing activity is very important for fisheries resource monitoring and spatial management. The environmental preferences of tropical tuna purse seine fleet in the Western and Central Pacific Ocean (WCPO) were constructed and compared at different spatial scales based on the fishing effort (FE) data from the available automatic identification system (AIS) and commercial fishery data compiled from the Western and Central Pacific Fisheries Commission (WCPFC), using maximum entropy (MaxEnt) methods. The MaxEnt models were fitted with FE and commercial fishery data and remote sensing environmental data. Our results showed that the area under the curve (AUC) value each month based on the commercial fishery data (1°) and FE at 0.25° and 0.5° spatial scales was greater than 0.8. The AUC values each month based on the FE data at a 1° scale ranged from 0.775 to 0.829. The AUC values based on commercial fishing data at the 1° scale were comparable to the model results based on FE data at the 0.5° scale and inferior to the model results based on FE data at the 0.25° scales. Overall, the sea surface temperature (SST), temperature at 100 metres (T100), oxygen concentration at 100 metres (O100) and total primary production (PP) had the greatest influence on the distribution of the purse seine tuna fleet. The oxygen concentration at 200 metres (O200), distance to shore (DSH), dissolved oxygen (Dox), EKE, mixed layer depth (Mld), sea surface salinity (SSS), salinity at 100 metres (S100) and salinity at 200 metres (S200) had moderate influences, and other environmental variables had little influence. The suitable habitat areas varied in response to environmental conditions. The purse seine tuna fleet was mostly present at locations where the SST, T100, O100, O200 and PP were 28–30 °C, 27–29 °C, 150–200 mmol/m3 and 5–10 mg/m−3, respectively. The MaxEnt models enable the integration of AIS data and high-resolution environmental data from satellite remote sensing to describe the spatiotemporal distribution of the tuna purse seine fishery and the influence of environmental variables on the distribution, and can provide forecasts for fishing ground distributions based on future remote sensing environmental data.

Synergistic relationship or not? Understanding the resilience and efficiency of the tourism economy: evidence from Hainan Province, China - Pengfei Zhang; Hu Yu; Linlin Xu; Wei Guo; Mingzhe Shen (Environment, Development and Sustainability, 2023)

Methylmercury promotes oxidative stress and autophagy in rat cerebral cortex: Involvement of PI3K/AKT/mTOR or AMPK/TSC2/mTOR pathways and attenuation by N-acetyl-L-cysteine - Yanfeng Wei; Linlin Ni; Jingjing Pan; Xiaoyang Li; Yu Deng; Bin Xu; Tianyao Yang; Jingyi Sun; Wei Liu (Neurotoxicology and Teratology, 2023)

Pahs emission characteristics and the mitigation in the valuable products from used mineral oil thermolysis recycling - Linlin Xu; Jie Yu; Gan Wan; Lushi Sun (Fuel, 2023)

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Talaromyces marneffei Infections in 8 Chinese Children with Inborn Errors of Immunity - Linlin Wang; Ying Luo; Xiaolin Li; Yixian Li; Yu Xia; Tingyan He; Yanyan Huang; Yongbin Xu; Zhi Yang; Jiayun Ling; Ruohang Weng; Xiaona Zhu; et al. (Mycopathologia, 2022)
Purpose Talaromyces marneffei (TM) is an opportunistic fungus leading to multi-organ damages and poor prognosis in immunocompromised individuals. TM infections in children are rare and our knowledge to TM infection is insufficient. To investigate the clinical characteristics of TM-infected children and to explore the underlying mechanisms for host against TM, we analysed TM-infected patients diagnosed in our hospital. Methods Eight patients with TM infections have been identified in Shenzhen Children’s Hospital during 2017–2021. Clinical data were collected from medical records. Immunological features were evaluated by flow cytometry. Literatures were also reviewed to summarize the reported inborn errors of immunity (IEIs) with TM infections. Results All 8 children were HIV-negative. The most common symptom of TM infections was fever (8/8), followed by weight loss (7/8), pneumonia (7/8), hepatomegaly (7/8), splenomegaly (6/8), anemia (6/8), lymphadenopathy (5/8), thrombocytopenia (3/8), diarrhea (3/8), rashes or skin lesions (3/8), and osteolytic lesions (1/8). Five children died during the follow-ups. CD3+ T cells were decreased in 6 patients. Eight patients had reduced natural killer cells. All patients went gene sequencing and were finally diagnosed as IEIs, including STAT1 gain-of-function, IL-2 receptor common gamma chain deficiency, adenosine deaminase deficiency, CD40 ligand deficiency, and STAT3 deficiency. Another 4 types of IEIs (CARD9, IFN- γ receptor 1, RelB, and NFKB2 deficiency), have been reported with TM infections based on literature review. Conclusion TM infections resulted in systemic injuries and high mortality. The spectrum of IEIs underlying TM infections indicated that T cell-mediated immunity, IFN- γ , IL-17 signalings and NF-κB pathways were important for host responses against TM infection. In reverse, for HIV-negative children without other secondary immunodeficiencies, IEIs should be considered in TM-infected children.

Associations of urinary polycyclic aromatic hydrocarbon metabolites and blood pressure with the mediating role of cytokines: A panel study among children - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Jie Yu; Shuang Chen; Meng Li; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Environmental Science and Pollution Research, 2022)

The Structure and Function of Microbial Community in Rhizospheric Soil of American Ginseng (Panax quinquefolius L.) Changed with Planting Years - Guozhong Chen; Ying Xue; Xin Yu; Chongwei Li; Yuping Hou; Hongwei Zhu; Linlin Jiang; Weibo Zheng; Zhibin Feng; Youzhi Li; Wenli Tang; Xiaoyu Zhao; et al. (Current Microbiology, 2022)

Deep-Sea-Derived Fungi as Valuable Producers of Cytotoxic Secondary Metabolites and Their Leads Potential - Guangrong Zhao; Wenli Tang; Jianlong Zhang; Peimin Shi; Youzhi Li; Jiao Wang; Qingqin Shen; Haixia Si; Linlin Jiang; Xin Yu; Hongwei Zhu; Guozhong Chen; et al. (Frontiers in Marine Science, 2022)
Cancer is the leading lethal disease worldwide. Natural products have contributed significantly to the development of approved therapeutic agents. Therefore, research into new bioactive naturally sourced metabolites with lead potential is urgently needed. It is well-known that marine microorganisms are by far one of the most notable and prolific sources of bioactive natural products. Among them, deep-sea-derived fungi are extraordinarily adapted and metabolically active under extreme environmental conditions, which enable them to produce a large number of novel secondary metabolites. Chemical examination of deep-sea-derived fungi has yielded enormous amounts of cytotoxic natural products and potential drug leads. This review summarizes a total of 229 cytotoxic compounds isolated from deep-sea-derived fungi from 2010 to 2021. The emphasis is on the unique chemical diversity of these metabolic products, together with their relevant cytotoxic properties. Among the isolated metabolites, 82 compounds have been found to possess moderate to potent cytotoxic activities. Meanwhile, we also highlight some compounds with potent cytotoxicities (namely “star molecules”) considering their high drug lead potential. This review reveals deep-sea-derived fungi as considerable resources for the development of new drugs and the potential of the newly discovered secondary metabolites as valuable antitumor lead compounds.

Electroporation-Based CRISPR/Cas9 Mosaic Mutagenesis of β-Tubulin in the Cultured Oyster - Jiulin Chan; Wei Zhang; Yue Xu; Yu Xue; Linlin Zhang (Frontiers in Marine Science, 2022)
Genome editing using clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 is enabling genetics improvement of productive traits in aquaculture. Previous studies have proven CRISPR/Cas9 to be feasible in oyster, one of the most cultured shellfish species. Here, we applied electroporation-based CRISPR/Cas9 knockout of β-tubulin and built a highly efficient genome editing system in Crassostrea gigas angulate . We identified the β-tubulin gene in the oyster genome and showed its spatiotemporal expression patterns by analyzing RNA-seq data and larval in situ hybridization. We further designed multiple highly specific guide RNAs (sgRNAs) for its coding sequences. Long fragment deletions were detected in the mutants by agarose gel electrophoresis screening and further verified by Sanger sequencing. In addition, the expression patterns of Cgβ-tubulin in the trochophore peritroch and intestinal cilia cells were altered in the mutants. Scanning electron microscopy represented shortened and almost complete depleted cilia at the positions of peritroch and the posterior cilium ring in Cgβ-tubulin mosaic knockout trochophores. Moreover, the larval swimming behavior in the mutants was detected to be significantly decreased by motility assay. These results demonstrate that β-tubulin is sufficient to mediate cilia development and swimming behavior in oyster larvae. By applying Cgβ-tubulin as a marker gene, our study established CRISPR/Cas9-mediated mosaic mutagenesis technology based on electroporation, providing an efficient tool for gene function validation in the oyster. Moreover, our research also set up an example that can be used in genetic engineering breeding and productive traits improvement in oysters and other aquaculture species.

Chromosome-Level Genome Assembly of Acanthogobius ommaturus Provides Insights Into Evolution and Lipid Metabolism - Yu Pan; Zhicheng Sun; Tianxiang Gao; Linlin Zhao; Na Song (Frontiers in Marine Science, 2022)
Acanthogobius ommaturus is a large, fast-growing annual fish widely distributed in coastal and estuarine areas. The adults will die after breeding, and its life cycle is only 1 year. The first chromosome-level genome assembly of A. ommaturus was obtained by PacBio and Hi-C sequencing in this study. The final genome assembly after Hi-C correction was 921.49 Mb, with contig N50 and scaffold N50 values of 15.70 Mb and 40.99 Mb, respectively. The assembled sequences were anchored to 22 chromosomes by using Hi-C data. A total of 18,752 protein-coding genes were predicted, 97.90% of which were successfully annotated. Benchmarking Universal Single-Copy Orthologs (BUSCO) assessment results for genome and gene annotations were 93.6% and 84.6%, respectively. A. ommaturus is phylogenetically closely related to Periophthalmodon magnuspinnatus and Boleophthalmus pectinirostris , diverging approximately 31.9 MYA with the two goby species. The A. ommaturus genome displayed 597 expanded and 3,094 contracted gene families compared with the common ancestor. A total of 1,155 positive selected genes (PSGs) ( p < 0.05) were identified. Based on comparative genomic analyses, we obtained several expanded genes such as acsbg2 , lrp1 , lrp6 , and znf638 involved in lipid metabolism. A total of twenty candidate genes were identified under positive selection, which associated with lifespan including ercc6 , igf1 , polg , and tert . Interspecific collinearity analysis showed a high genomic synteny between A. ommaturus and P. magnuspinnatus . The effective population size of A. ommaturus decreased drastically during 200–100 Ka because of Guxiang ice age and then increased gradually following warm periods. This study provides pivotal genetic resources for in-depth biological and evolutionary studies, and underlies the molecular basis for lipid metabolism.

Bak interacts with AKT and is involved in TNFα/CHX-induced apoptosis - Jiayue Song; Fuqiang Zhang; Yu Wang; Yuxiang Wang; Jingtian Zhang; Zixuan Xiao; Xueqi Fu; Xuemin Xu; Linlin Zeng (Molecular and Cellular Biochemistry, 2022)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Functional Trait Responses of Macrobenthos to Anthropogenic Pressure in Three Temperate Intertidal Communities - Jian-Yu Dong; Linlin Zhao; Xiaolong Yang; Xin Sun; Xiumei Zhang (Frontiers in Marine Science, 2021)
With the increasing impact of human activities on marine ecosystems, there is a growing need to assess how the components of marine ecosystems (e.g., macrobenthos) respond to these anthropogenic pressures. In this work, the trait-based approach was used to assess the effects of anthropogenic pressures represented by the area of land-based aquaculture pond (Pond Area) and heavy metals on the macrobenthic communities in three intertidal zones[Aoshan Bay (AO), Wenquan River and Daren River (RW), and Xiaodao Bay (XD)] of Laoshan Bay, Shandong Peninsula, China. Compared with RW and XD, AO was under more pressure in terms of the average concentrations of heavy metals and total organic carbon (TOC) in sediments and also in the Pond Area. Fuzzy correspondence analysis (FCA) showed that there were significant differences in the composition of functional traits among the three regions (PERMANOVA; p < 0.05). In the highly polluted area, macrobenthic communities exhibited a combination of traits, such as relatively short life span, weak mobility, feeding on deposits, and more tolerant to organic matter, whereas in a less polluted area, they exhibited a combination of traits, such as relatively long life span, relatively high mobility, and more sensitivity to organic matter. The RDA results showed that the distribution of the trait modalities was significantly affected by heavy metals (Hg and Cd), TOC, Pond Area, and sampled location. Variation partitioning analysis (VPA) indicated that the shared influence of sediment-related pollution factors and Pond Area contributed most to the variance of the functional traits, which implied that human activities directly and/or indirectly lead to changes in functional traits of macrobenthic communities in the intertidal zones.

Metabolism and antioxidation regulation of total flavanones from Sedum sarmentosum Bunge against high-fat diet-induced fatty liver disease in Nile tilapia (Oreochromis niloticus) - Kai Yu; Kai Huang; Zhanyang Tang; Xiuyun Huang; Linlin Sun; Linxing Pang; Cuiqin Mo (Fish Physiology and Biochemistry, 2021)

A July-August relative humidity record in North China since 1765 AD reconstructed from tree-ring cellulose δ18O - Linlin Cui; Yu Liu; Qiang Li; Huiming Song; Congxi Fang (International Journal of Biometeorology, 2021)

Relationship between heavy metal consolidation and H2S removal by biochar from microwave pyrolysis of municipal sludge: effect and mechanism - Qingyuan Lin; Jun Zhang; Linlin Yin; Hao Liu; Wei Zuo; Yu Tian (Environmental Science and Pollution Research, 2021)

A Role for Transmembrane Protein 16C/Slack Impairment in Excitatory Nociceptive Synaptic Plasticity in the Pathogenesis of Remifentanil-induced Hyperalgesia in Rats - Yize Li; Linlin Zhang; Jing Li; Chunyan Wang; Yi Chen; Yuan Yuan; Keliang Xie; Guolin Wang; Yonghao Yu (Neuroscience Bulletin, 2021)

Effect of divalent manganese (Mn2+) concentration on the growth and nitrate nitrogen content of lettuce during aeroponic intercropping with cherry radish - Lei Zhang; Linlin Wang; Faqinwei Li; Fei Xiao; Haiye Yu (Horticulture, Environment, and Biotechnology, 2021)

Black Soldier Fly (Hermetia illucens) Larvae Significantly Change the Microbial Community in Chicken Manure - Xingxiao Zhang; Junzhe Zhang; Linlin Jiang; Xin Yu; Hongwei Zhu; Jianlong Zhang; Zhibin Feng; Xiang Zhang; Guozhong Chen; Zhijian Zhang (Current Microbiology, 2021)

Quantitative assessment on soil concentration of heavy metal–contaminated soil with various sample pretreatment techniques and detection methods - Fei Pan; Yong Yu; Lei Yu; Hailan Lin; Yeyao Wang; Linlin Zhang; Dawei Pan; Rilong Zhu (Environmental Monitoring and Assessment, 2020)

High throughput detection of antibiotic residues in milk by time-resolved fluorescence immunochromatography based on QR code - Asha Ashuo; Wenjia Zou; Jingjie Fu; Tengkun Yang; Linlin Yu; Wei Liu; Liu Yang; Ghulam Mujtaba Mari; Haiyang Jiang (Food Additives & Contaminants: Part A, 2020)

An Improved Coal Permeability Model with Variable Cleat Width and Klinkenberg Coefficient - Gang Wang; Zhiyong Xiao; Junhong Yu; Lu Zhang; Linlin Sun (Geotechnical and Geological Engineering, 2020)

Correction to: Microbial synergy and stoichiometry in heap biooxidation of low-grade porphyry arsenic-bearing gold ore - Jiafeng Li; Linlin Tong; Yu Xia; Hongying Yang; Wolfgang Sand; Hongzhen Xie; Bibo Lan; Shuiping Zhong; Ali Auwalu (Extremophiles, 2020)

Microbial synergy and stoichiometry in heap biooxidation of low-grade porphyry arsenic-bearing gold ore - Jiafeng Li; Linlin Tong; Yu Xia; Hongying Yang; Wolfgang Sand; Hongzhen Xie; Bibo Lan; Shuiping Zhong; Ali Auwalu (Extremophiles, 2020)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

Effects of drought–re-watering–drought on the photosynthesis physiology and secondary metabolite production of Bupleurum chinense DC. - Linlin Yang; Yu Zhao; Qi Zhang; Lin Cheng; Mei Han; Yueying Ren; Limin Yang (Plant Cell Reports, 2019)

Optimizing cold storage of the ectoparasitic mite Pyemotes zhonghuajia (Acari: Pyemotidae), an efficient biological control agent of stem borers - Limin He; Litao Li; Lichen Yu; Xiong Z. He; Rui Jiao; Changxin Xu; Linlin Zhang; Jinli Liu (Experimental and Applied Acarology, 2019)

Ozonation catalyzed by iron- and/or manganese-supported granular activated carbons for the treatment of phenol - Wei Xiong; Nan Chen; Chuanping Feng; Yang Liu; Ningping Ma; Jian Deng; Linlin Xing; Yu Gao (Environmental Science and Pollution Research, 2019)

A miR-511-binding site SNP in the 3′UTR of IGF-1 gene is associated with proliferation and apoptosis of PK-15 cells - Wenzhen Wei; Gang Wang; Yunyun Cheng; Rui Yang; Jie Song; Shan Huang; Haoyang Li; Hongwei Geng; Hao Yu; Songcai Liu; Linlin Hao (In Vitro Cellular & Developmental Biology - Animal, 2019)

Effect of supersaturation on the oral bioavailability of paclitaxel/polymer amorphous solid dispersion - Linlin Miao; Yuheng Liang; Wenli Pan; Jingxin Gou; Tian Yin; Yu Zhang; Haibing He; Xing Tang (Drug Delivery and Translational Research, 2019)

Effects of artificial aeration and iron inputs on the transformation of carbon and phosphorus in a typical wetland soil - Linlin Zhang; Ze Tang; Sijian Zhang; Xueying Jia; Xiaofei Yu; Guangzhi Sun; Yuanchun Zou (Journal of Soils and Sediments, 2018)

Insight into the effects of biochar as adsorbent and microwave receptor from one-step microwave pyrolysis of sewage sludge - Jun Zhang; Yu Tian; Linlin Yin; Jie Zhang; Jörg E. Drewes (Environmental Science and Pollution Research, 2018)

Synaptobrevin-2 facilitates the trafficking and function of atrial SK2 channel - Tao Li; Xuehui Fan; Yiyan Yu; Linlin Chen; Wenjun Huang; Yan Yang; Jimin Cao; Xiaorong Zeng; Xiaoqiu Tan (Science China Life Sciences, 2018)

Linkage disequilibrium and functional analysis of PRE1 insertion together with SNPs in the promoter region of IGFBP7 gene in different pig breeds - Qingyan Wu; Hao Yu; Wenzhen Wei; Yunyun Cheng; Shan Huang; Hongyu Shi; Songcai Liu; Jichao Xia; Hongyao Jia; Linlin Hao (Journal of Applied Genetics, 2018)

Labile organic carbon fractions and carbon pool management index in a 3-year field study with biochar amendment - Xu Yang; Di Wang; Yu Lan; Jun Meng; Linlin Jiang; Qiang Sun; Dianyun Cao; Yuanyuan Sun; Wenfu Chen (Journal of Soils and Sediments, 2018)

5-Azacytidine treatment and TaPBF-D over-expression increases glutenin accumulation within the wheat grain by hypomethylating the Glu-1 promoters - Jiantang Zhu; Linlin Fang; Jiaqi Yu; Ying Zhao; Fanguo Chen; Guangmin Xia (Theoretical and Applied Genetics, 2018)

The analgesic effect of trans-resveratrol is regulated by calcium channels in the hippocampus of mice - Weijie Wang; Yingcong Yu; Jing Li; Lin Wang; Zhi Li; Chong Zhang; Linlin Zhen; Lianshu Ding; Gang Wang; Xiaoyang Sun; Ying Xu (Metabolic Brain Disease, 2017)

Investigation on the removal of H2S from microwave pyrolysis of sewage sludge by an integrated two-stage system - Jun Zhang; Yu Tian; Linlin Yin; Wei Zuo; Zhenlong Gong; Jie Zhang (Environmental Science and Pollution Research, 2017)

Disposition of Flavonoids for Personal Intake - Shuqiang Liu; Haihui Zheng; Rongjin Sun; Huangyu Jiang; Jiamei Chen; Jia Yu; Qisong Zhang; Qingwei Chen; Lijun Zhu; Ming Hu; Linlin Lu; Zhongqiu Liu (Current Pharmacology Reports, 2017)

Effects of maize stover and its derived biochar on greenhouse gases emissions and C-budget of brown earth in Northeast China - Xu Yang; Yu Lan; Jun Meng; Wenfu Chen; Yuwei Huang; Xiaoyi Cheng; Tianyi He; Ting Cao; Zunqi Liu; Linlin Jiang; Jiping Gao (Environmental Science and Pollution Research, 2017)

Characterization of Gastric Microbiota in Twins - Quanjiang Dong; Yongning Xin; Lili Wang; Xinying Meng; Xinjuan Yu; Linlin Lu; Shiying Xuan (Current Microbiology, 2017)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

Continued Studies on the Effects of Simazine on the Liver Histological Structure and Metamorphosis in the Developing Xenopus laevis - Linlin Sai; Binpeng Qu; Yan Li; Qiang Jia; Cunxiang Bo; Yanzhong Liu; Gongchang Yu; Lin Xie; Ling Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2016)

In Vivo Exposure of Kaempferol Is Driven by Phase II Metabolic Enzymes and Efflux Transporters - Liang Zheng; Lijun Zhu; Min Zhao; Jian Shi; Yuhuan Li; Jia Yu; Huangyu Jiang; Jinjun Wu; Yunli Tong; Yuting Liu; Ming Hu; Linlin Lu; et al. (The AAPS Journal, 2016)

CspE is Overproduced by Temperature Downshift in the Acinetobacter johnsonii DBP-3 - Dan Su; Linlin Hao; Fuwang Chen; Siming Li; Ahmed Mohamed Abdelrahman; Yu Zhang; Hao Yu; Songcai Liu; Mingtang Li (Current Microbiology, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

TsMIP6 enhances the tolerance of transgenic rice to salt stress and interacts with target proteins - Linlin Sun; Guohong Yu; Xiaori Han; Shichao Xin; Xiaojing Qiang; Linlin Jiang; Shuhui Zhang; Xianguo Cheng (Journal of Plant Biology, 2015)

Pygo2 siRNA Inhibit the Growth and Increase Apoptosis of U251 Cell by Suppressing Histone H3K4 Trimethylation - Mingcong Li; Linlin Chao; Jian Wu; Hao Xu; Shanghan Shen; Sifang Chen; Xin Gao; Ning Yu; Zhanxiang Wang (Journal of Molecular Neuroscience, 2015)

The Effects of Simazine, a Chlorotriazine Herbicide, on the Expression of Genes in Developing Male Xenopus laevis - Linlin Sai; Yanzhong Liu; Binpeng Qu; Gongchang Yu; Qiming Guo; Cunxiang Bo; Lin Xie; Qiang Jia; Yuezhong Li; Xiangxin Li; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Expression of neuropeptides and bone remodeling-related factors during periodontal tissue regeneration in denervated rats - Xijiao Yu; Linlin Lv; Jing Zhang; Ting Zhang; Changjie Xiao; Shu Li (Journal of Molecular Histology, 2015)

Genetic manipulation of a high-affinity PHR1 target cis-element to improve phosphorous uptake in Oryza sativa L. - Wenyuan Ruan; Meina Guo; Linlin Cai; Hongtao Hu; Changying Li; Yu Liu; Zhongchang Wu; Chuanzao Mao; Keke Yi; Ping Wu; Xiaorong Mo (Plant Molecular Biology, 2015)

Erratum to: Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Assessing Atrazine-Induced Toxicities in Bufo bufo gargarizans Cantor - Linlin Sai; Qingbo Wu; Binpeng Qu; Cunxiang Bo; Gongchang Yu; Qiang Jia; Lin Xie; Yuezhong Li; Qiming Guo; Jack C. Ng; Cheng Peng (Bulletin of Environmental Contamination and Toxicology, 2015)

Distribution of enterovirus 71 RNA in inflammatory cells infiltrating different tissues in fatal cases of hand, foot, and mouth disease - Pin Yu; Zifen Gao; Yuanyuan Zong; Linlin Bao; Lili Xu; Wei Deng; Yanfeng Xu; Zhancheng Gao; Yanfeng Yao; Fengdi Li; Qi Lv; Chuan Qin (Archives of Virology, 2015)

Expression of tomato SlTIP2;2 enhances the tolerance to salt stress in the transgenic Arabidopsis and interacts with target proteins - Shichao Xin; Guohong Yu; Linlin Sun; Xiaojing Qiang; Na Xu; Xianguo Cheng (Journal of Plant Research, 2014)

Oxidative stress promotes d-GalN/LPS-induced acute hepatotoxicity by increasing glycogen synthase kinase 3β activity - Linlin Wei; Feng Ren; Xiangying Zhang; Tao Wen; Hongbo Shi; Sujun Zheng; Jing Zhang; Yu Chen; Yuanping Han; Zhongping Duan (Inflammation Research, 2014)

Transcriptomic analysis reveals key regulators of mammogenesis and the pregnancy-lactation cycle - YuanYuan Zhou; Wei Gong; JingFa Xiao; JiaYan Wu; LinLin Pan; XiaoNuan Li; XuMin Wang; WeiWei Wang; SongNian Hu; Jun Yu (Science China Life Sciences, 2014)

The characteristics of epithelial cell rests of Malassez during tooth eruption of development mice - Yanzhi Wang; Linlin Lv; Xijiao Yu; Ting Zhang; Shu Li (Journal of Molecular Histology, 2014)

Lanthanum chloride impairs spatial learning and memory and downregulates NF-κB signalling pathway in rats - Linlin Zheng; Jinghua Yang; Qiufang Liu; Fei Yu; Shengwen Wu; Cuihong Jin; Xiaobo Lu; Lifeng Zhang; Yanqiu Du; Qi Xi; Yuan Cai (Archives of Toxicology, 2013)

Calcium accumulation characterization in the aerobic granules cultivated in a continuous-flow airlift bioreactor - Dandan Zhou; Mengyuan Liu; Linlin Gao; Chunyan Shao; Jie Yu (Biotechnology Letters, 2013)

PEGylated Multi-Walled Carbon Nanotubes for Encapsulation and Sustained Release of Oxaliplatin - Linlin Wu; Changjun Man; Hong Wang; Xiaohe Lu; Qinghai Ma; Yu Cai; Wanshan Ma (Pharmaceutical Research, 2013)

Inducible regulation of GDNF expression in human neural stem cells - ShuYan Wang; Ping Ren; YunQian Guan; ChunLin Zou; LinLin Fu; Yu Zhang (Science China Life Sciences, 2013)

Transcriptome profiling of the developing postnatal mouse testis using next-generation sequencing - Wei Gong; LinLin Pan; Qiang Lin; YuanYuan Zhou; ChengQi Xin; XiaoMin Yu; Peng Cui; SongNian Hu; Jun Yu (Science China Life Sciences, 2013)

Large-scale collection and annotation of gene models for date palm (Phoenix dactylifera, L.) - Guangyu Zhang; Linlin Pan; Yuxin Yin; Wanfei Liu; Dawei Huang; Tongwu Zhang; Lei Wang; Chengqi Xin; Qiang Lin; Gaoyuan Sun; Mohammed M. Ba Abdullah; Xiaowei Zhang; et al. (Plant Molecular Biology, 2012)

High-throughput sequencing-based gene profiling on multi-staged fruit development of date palm (Phoenix dactylifera, L.) - Yuxin Yin; Xiaowei Zhang; Yongjun Fang; Linlin Pan; Gaoyuan Sun; Chengqi Xin; Mohammed M. Ba Abdullah; Xiaoguang Yu; Songnian Hu; Ibrahim S. Al-Mssallem; Jun Yu (Plant Molecular Biology, 2012)

Growth inhibition induced by transforming growth factor-β1 in human oral squamous cell carcinoma - Xiumei Wang; Wenjing Sun; Jing Bai; Linlin Ma; Yang Yu; Jingshu Geng; Jiping Qi; Zhongcheng Shi; Songbin Fu (Molecular Biology Reports, 2009)